The Problems of Geographical Indication of Goods in Procurement to Meet State and Municipal Requirements - A. Ye. Yuritsin; Yu. B. Lavrov (Сибирское юридическое обозрение, 2015)
Basing on the study of national experience of applying the Federal Law "On the contract system in the procurement of goods, works and services for state and municipal needs" the authors explore current problems of geographical indication of goods as a part of the application-form used in the online auction and suggest their solutions.